Analisis Kualitas Drainase Terhadap Kerusakan Dini Perkerasan Lentur (Study Kasus Ruas Jalan Solo - Jogja Km 15+000 - Km 15+500) - Pramudya, Unggul Pramudya; , Jaji Abdurrosyid, ST., MT (2016)
The road is one of the most vital transportation infrastructure in order to carry out the relationships between / across from one region to another region, where roads were cut off access to the area will be isolated, making it difficult to follow the developing areas connected with good road access. Hence the need for an investigation into the cause of the damage early, so the service roads can be improved. This study aims to determine the effect of drainage on the quality of flexible pavement damage. This study uses a PCI (Pavement Condition Index) as the parameter of damage, while the quality of drainage using analytical meode considering the discharge of rain water as drainage quality parameters. The research location is in the way Solo - Jogja in from Km 15 + 000 and ends at Km 15 + 500. In the data processing required two types of data, namely primary and secondary. Stages of this research consisted of seven stages of the research, which produces how drainage quality comparison with the level of damage that can be from a table overflowing with PCI relations debit. Based on analysis of the condition of pavement roads Solo - Jogja Km 15 + 000 - Km 15 + 500 can be said to suffer from premature deterioration , because of the comparison of pavement conditions well drained soil with an object , showing the value of PCI smaller than the roads are well drained ( roads Solo - Jogja Km 14 + 500 - Km 14 + 600 ) . The influence of the quality of drainage in flexible pavement visible from water runoff grafi relation to the value of PCI . Based on the graph shows the greater discharge rainwater runoff smaller value of PCI obtained . It is strengthened by ketidaktersedinya drainage facilities and geometric conditions are unfavorable , then the need for an alternative form of procurement handling drainage problems drainage and road geometric improvements . Dimensional channel has a width of 0.7 m , a depth of 0.35 m , and 0,105 m high surveillance in order to be able to accommodate the discharge of rain return period 10 years . Keywords : Damage, pavement conditions, drainage, Solo - Jogja.